Ekspektasi Hasil dan Dukungan Sosial dalam Minat Karier Mengajar pada Generasi Muda: Suatu Meta-Analisis. - Suwarsito; Widodo; Merry Lapasau; Sumaryoto; Supardi Uki Sajiman (Jurnal Penelitian Pendidikan IPA, 2026)
The declining interest of young people in the teaching profession has raised concerns about the sustainability of the future education workforce. Grounded in Social Cognitive Career Theory (SCCT), this study synthesizes empirical evidence on the relationships between outcome expectancy, social support, and teaching career interest through a meta-analysis. Following PRISMA 2020 guidelines, relevant studies published between 2017 and 2025 were systematically identified from Scopus, Web of Science, ERIC, and Google Scholar. A total of 20 empirical studies involving 10,527 participants met the inclusion criteria and were analyzed using a random-effects model with Fisher’s z transformation.The results show that outcome expectancy has a significant moderate-to-large association with teaching career interest (r = 0.43), while social support demonstrates a significant moderate association (r = 0.35). Heterogeneity was moderate for outcome expectancy (I² = 48.7%) and low-to-moderate for social support (I² = 30.3%). Visual inspection of funnel plots suggests no substantial publication bias. These findings provide robust support for SCCT and offer theoretical and practical insights into factors influencing youth interest in the teaching profession.